Assistance in Developing a Digital-Based Management System to Improve Documentation Quality and Motivation of Internship Student Adi Sumarmo VHS - Rasyid Sidik; Muhammad Kholil; Azizah Nurul Husnaini; Indah Widiastuti; Valiant Lukad Perdana Sutrisno; Yuyun Estriyanto; Taufik Wisnu Saputra; Budi Harjanto; Ngatou Rohman (Engagement: Jurnal Pengabdian Kepada Masyarakat, 2026)
Background: The implementation of industrial internships at Adi Sumarmo VHS, based on a CIPP evaluation, has not utilized information technology to address issues in internship documentation, limited monitoring, and the orderliness of recording student internship activity. Purpose of Study: This community service program is carried out to help the community develop a digital-based internship management system to improve the quality of industrial internship document recording. With this improvement, it is expected to motivate students to undertake industrial internships. Methods: This service integrates a community participatory approach into the 4D development model, so that in the define, design, develop, and disseminate stages, there is one or two team actions in the form of assistance and socialization. This integration aims to build a positive perception of the Technology Acceptance Model (TAM) in the community. Result: The program's participants gained community experience through active participation in mentoring activities to solve industrial internship problems by implementing information technology solutions. The outcome obtained was an industrial internship management information system with a feasibility score of 4.8/5 (96%) from the assessment of 3 IT experts. This service is also considered beneficial for teachers and students, with index scores of 90.75% and 80% based on solutions generated through an active community-participatory approach. In the end, service can empower the community to organize digital services that support more orderly documentation, thereby increasing students' motivation to undertake industrial internships as a form of documented achievement.